2017
DOI: 10.3389/fpls.2017.00725
|View full text |Cite
|
Sign up to set email alerts
|

Miniature Inverted Repeat Transposable Element Insertions Provide a Source of Intron Length Polymorphism Markers in the Carrot (Daucus carota L.)

Abstract: The prevalence of non-autonomous class II transposable elements (TEs) in plant genomes may serve as a tool for relatively rapid and low-cost development of gene-associated molecular markers. Miniature inverted-repeat transposable element (MITE) copies inserted within introns can be exploited as potential intron length polymorphism (ILP) markers. ILPs can be detected by PCR with primers anchored in exon sequences flanking the target introns. Here, we designed primers for 209 DcSto (Daucus carota Stowaway-like) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…We set the number of assumed populations (K values) from 1 to 11 and the length of burn-in to 100,000 followed by 500,000 Monte Carlo iterations. The most likely number of clusters (K) was estimated as described by Stelmach et al [ 48 ]. To define the number of principal components needed to control population stratification, we performed Tracy–Widom statistics on PCA eigenvalues using ‘LEA‘ R package v.2.6.0 [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…We set the number of assumed populations (K values) from 1 to 11 and the length of burn-in to 100,000 followed by 500,000 Monte Carlo iterations. The most likely number of clusters (K) was estimated as described by Stelmach et al [ 48 ]. To define the number of principal components needed to control population stratification, we performed Tracy–Widom statistics on PCA eigenvalues using ‘LEA‘ R package v.2.6.0 [ 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Apart from SSRs, sequence-based markers developed in carrot can be exemplified with the works of Iorizzo et al [32] and Stelmach et al [33], where 4000 single nucleotide polymorphism (SNP) and 209 Intron Length Polymorphism (ILP) markers were developed, respectively. A hybridization-based genotyping strategy, DArT (Diversity Arrays Technology) genotyping, was also applied on carrot [34].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, in the current study, MITE3321 insertions were found in both analyzed pine species, belonging to separate subgenera, suggesting similar distributions also in other pine species. Therefore, MITE3321 could be a useful molecular marker for genotyping of pine species, as shown for MITEs in other plant species [48,140,141].…”
Section: Discussionmentioning
confidence: 99%